2020
DOI: 10.1149/1945-7111/abbbbe
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Degradation of LiFePO4/Graphite Cells: The Impact of Water Contamination and an Evaluation of Common Electrolyte Additives

Abstract: LiFePO4 (LFP) is an appealing cathode material for Li-ion batteries. Its superior safety and lack of expensive transition metals make LFP attractive even with the commercialization of higher specific capacity materials. In this work the performance of LFP/graphite cells is tested at various temperatures and cycling protocols. The amount of water contamination is controlled to study the impact of water on capacity fade in LFP. Further, several additive systems that have been effective in NMC/graphite chemistrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 57 publications
5
82
0
Order By: Relevance
“…However, it introduces several challenges when being utilized as a battery material, specifically that the composition is highly sensitive to the synthesis parameters, which can have a negative impact on properties (You et al, 2014;You et al, 2015;Rudola et al, 2017;Chen et al, 2018;Li et al, 2019). For example, Prussian white (PW) with ideal composition Na 2 Fe [Fe(CN) 6 ] has a theoretical capacity of 170 mAh g −1 and an average voltage output of ~3.2 V, which is comparable with the specific energy density achievable for LiFePO 4 (Wang et al, 2015;Logan et al, 2020). However, achieving this capacity is extremely difficult due to the presence of [Fe(CN) 6 ] n− vacancies (Hurlbutt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it introduces several challenges when being utilized as a battery material, specifically that the composition is highly sensitive to the synthesis parameters, which can have a negative impact on properties (You et al, 2014;You et al, 2015;Rudola et al, 2017;Chen et al, 2018;Li et al, 2019). For example, Prussian white (PW) with ideal composition Na 2 Fe [Fe(CN) 6 ] has a theoretical capacity of 170 mAh g −1 and an average voltage output of ~3.2 V, which is comparable with the specific energy density achievable for LiFePO 4 (Wang et al, 2015;Logan et al, 2020). However, achieving this capacity is extremely difficult due to the presence of [Fe(CN) 6 ] n− vacancies (Hurlbutt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that residual moisture (25–50 ppm) in LiPF 6 ‐based electrolytes can lead to more homogenous SEIs on deposited Lithium electrodes [19] . Logan et al [20] . discovered that LFP/graphite cells tolerated moistures of ca.…”
Section: Introductionmentioning
confidence: 99%
“…chose 120 °C for post‐drying both NCM cathodes with PVDF and graphite anodes with PVDF, but did not provide details about vacuum level or post‐drying time. Logan et al [26] . stated that they post‐dried LiFePO 4 /artificial graphite cells for 14 hours between 100 °C and 120 °C under vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5g, the full cell containing recycled graphite exhibits charge/discharge curves similar to those of the commercial references, featuring capacities of 115.5 and 105.3 mA h g −1 after 100 and 500 cycles, respectively. 73,74 Capacity decay took place slowly, and capacitance retention was stabilized eventually at approximately 85% after 500 cycles with a high CE value of ∼99.7% (Figure 5h). This performance can cater to the commercial requirements well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%